PERANCANGAN FORMULASI DAN IMPLEMENTASI STRATEGI BISNIS PADA UMKM VIFLORISTT SUBANG - Maudy Anesha Putri; Mutqi Sopiawadi; Nopa Nurdiansyah; Sri Asti Wulandari; Widia Salshadila; Susi Wulandari; Ade Guntara Fauzi; Rossa Yunifa (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to formulate and implement appropriate business strategies for Vifloristt, an online florist MSME in Subang, to strengthen competitiveness in the digital market. A qualitative descriptive method was used through interviews, observation of digital activities, and document review. Internal and external conditions were analyzed using the SWOT framework supported by IFAS and EFAS matrices. The results show that Vifloristt has strengths in creative product design, responsive services, and brand recognition, while weaknesses include limited resources and simple financial recording systems. Externally, the growth of online shopping and social-media promotion creates strong opportunities, although intense competition and fluctuating raw-material prices remain threats. Strategic recommendations are formulated to optimize strengths, reduce weaknesses, and support sustainable business growth.